PENGARUH PERSEPSI TEKNOLOGI INFORMASI DAN FITUR LAYANAN TERHADAP MINAT NASABAH MENGGUNAKAN INTERNET BANKING (STUDI KASUS PADA NASABAH BANK BRI) - Intan Sri Asti; Suyanto Suyanto; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This study aims to explain the effect of perceptions of information technology and service features on customers' interest in using internet banking. Samples taken are 96 customers of BRI bank as respondents who have used internet banking at least once. This research is quantitative in nature. The method used in sampling is nonprobability sampling and the method used is purposive sampling. Meanwhile, the analysis technique used is multiple linear regression with the help of the SPSS version 25 program. Based on the research that has been done, it is found that perceptions of information technology and service features affect customer interest in using internet banking. Keywords: Perceptions of information technology, service features, and customer interest in using internet banking